Association of oxidative stress and DNA damage with grafting time in patients with multiple myeloma and lymphoma submitted to autologous hematopoietic stem cell transplantation - Santos,Thayna Nogueira dos (2016)
ABSTRACT The aim of the study was to investigate the association between oxidative stress and DNA damage with grafting time in patients submitted to autologous hematopoietic stem-cell transplantation (HSCT). The study included 37 patients submitted to autologous HSCT diagnosed with Multiple Myeloma (MM) and lymphoma (Hodgkin’s and non-Hodgkin’s). Biomarkers of oxidative stress and DNA damage index (DI) were performed at baseline (pre-CR) of the disease and during the conditioning regimen (CR), one day after the HSCT, ten days after HSCT and twenty days after HSCT, as well as in the control group consisting of 30 healthy individuals. The outcomes showed that both groups of patients had an hyperoxidative state with high DI when compared to baseline and to the control group and that the CR exacerbated this condition. However, after the follow-up period of the study, this picture was re-established to the baseline levels of each pathology. The study patients with MM showed a mean grafting time of 10.75 days (8 to 13 days), with 10.15 days (8 to 15 days) for the lymphoma patients. In patients with MM, there was a negative correlation between the grafting time and the basal levels of GPx (r = -0.54; p = 0.034), indicating that lower levels of this important enzyme are associated with a longer grafting time. For the DI, the correlation was a positive one (r = 0.529; p = 0.030). In the group with lymphoma, it was observed that the basal levels of NOx were positively correlated with grafting time (r = 0.4664, p = 0.032). The data indicate the potential of these biomarkers as predictors of toxicity and grafting time in patients with MM and Lymphomas submitted to autologous HSCT.